The Effect of Denatured Albumin with Concentrated Growth Factors in Minimally Invasive Sinus Piezosurgery: Preliminary Pilot Study Results - Ntontoulos, Vasileios; Dabarakis, Nikolaos (European Journal of Dentistry, 2023)
A new protocol with albumin-concentrated growth factor (CGF) is investigated through Piezosurgery as a minimally invasive alternative to sinus-floor-augmentation that is associated with high morbidity and high incidence of sinusitis. The clinical sample consists of five patients (three men and two women) with an average age of 53.75 ± 3.59 years and a mean height of 3.7 ± 1.22 mm of residual bone. The Piezo-Alb-CGF protocol consists of a minimally invasive transcrestal approach with or without flap, piezosurgery preparation, applying the Schneiderian membrane's hydrodynamic detachment-elevation, injecting albumin-CGF into the sinus, optional bone grafting and implantation, and evaluation for 2 to 6 months postoperatively. Eight implants were placed without complications. After 4 to 6 months, cone-beam computed tomography and panoramic radiographs showed total osseointegration and the formation of new bone. In addition, a year of clinical follow-up was performed. There was a positive correlation between implant stability quotient values at all protocol stages. The significance level was 5%. Albumin-CGF regenerative protocol promotes new bone formation, reduces postoperative morbidity, and shortens healing time. It also offers a uniform and safe hydraulic membrane lift and bicortical implant fixation, even in cases with a residual bone height below 6 mm.
Keywords: bioengineering; sinus floor augmentations; Piezosurgery; serum albumin; dental implants